2014
DOI: 10.1021/am5047944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Topography and Bioactive Properties on Early Adhesion and Growth Behavior of Mouse Preosteoblast MC3T3-E1 Cells

Abstract: The effects of bioactive properties and surface topography of biomaterials on the adhesion and spreading properties of mouse preosteoblast MC3T3-E1 cells was investigated by preparation of different surfaces. Poly lactic-co-glycolic acid (PLGA) electrospun fibers (ES) were produced as a porous rough surface. In our study, coverslips were used as a substrate for the immobilization of 3,4-dihydroxyphenylalanine (DOPA) and collagen type I (COL I) in the preparation of bioactive surfaces. In addition, COL I was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 57 publications
0
38
1
Order By: Relevance
“…This concept has been experimentally supported using nanopatterned substrates that mimic topographic features encountered in the native extracellular basement. 5,7,14 Cells were cultured for 24 h on various nanopatterned substrates with different groove widths, and their morphological changes were observed. Cells showed an altered morphology dependent on not only the presence of nanopatterning, but also on the ratio of ridge and groove dimensions of these patterns (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This concept has been experimentally supported using nanopatterned substrates that mimic topographic features encountered in the native extracellular basement. 5,7,14 Cells were cultured for 24 h on various nanopatterned substrates with different groove widths, and their morphological changes were observed. Cells showed an altered morphology dependent on not only the presence of nanopatterning, but also on the ratio of ridge and groove dimensions of these patterns (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the PDOP coating can obviously increase the surface free energy of materials. Investigations have demonstrated that the PDOP coating has a binding effect on the extracellular matrix protein from the culture medium, which enhances the adhesion and proliferation of cells . In addition, the activity of MC3T3‐E1 cells on TiO 2 /PDOP/GA samples was decreased compared with that on TiO 2 /PDOP.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby a thin polydopamine film is formed that exhibits reactivity towards nucleophiles, such as thiols and amines. 4,12,13 Polydopamine modified materials can also be used to immobilize extracellular matrix (ECM) proteins, such as collagen type I 14 or serum proteins. 13 To create polydopamine coatings on biomaterials, a large amount of dopamine is needed.…”
Section: Introductionmentioning
confidence: 99%